2011
DOI: 10.1108/02683941111164508
|View full text |Cite
|
Sign up to set email alerts
|

Coworker reactions to observing sexual behavior at work

Abstract: PurposeThe goal of the present research is to investigate the association between observing consensual sexual behavior at work (e.g. flirting, joking) and job outcomes – specifically, job satisfaction and turnover intentions.Design/methodology/approachQuestionnaires were administered about observed consensual sexual behavior and job attitudes in two separate studies of working adults. Participants in Study 1 were 113 workers from 33 workplaces in the Midwestern USA; participants in Study 2 were 242 adults work… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
31
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 53 publications
4
31
0
Order By: Relevance
“…Both variables have been widely studied in management research due to their strong relationships with employee performance and turnover decisions (Griffeth et al, ; Meyer, Stanley, Herscovitch, & Topolnytsky, ). Consistent with previous SH research (e.g., Salvaggio, Hopper, & Packell, ; J. H. Williams et al, ; Willness et al, ), we propose that individuals’ perceptions of anti‐SH practices (experiences of SH) will be positively (negatively) related to affective commitment and intentions to stay.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 86%
“…Both variables have been widely studied in management research due to their strong relationships with employee performance and turnover decisions (Griffeth et al, ; Meyer, Stanley, Herscovitch, & Topolnytsky, ). Consistent with previous SH research (e.g., Salvaggio, Hopper, & Packell, ; J. H. Williams et al, ; Willness et al, ), we propose that individuals’ perceptions of anti‐SH practices (experiences of SH) will be positively (negatively) related to affective commitment and intentions to stay.…”
Section: Theoretical Background and Hypothesessupporting
confidence: 86%
“…The psychological and structural context of work, such as the norms for sexual behaviour, are more relevant for understanding workplace romance than basic demographic characteristics of employees such as age or gender ratios (Salvaggio et al . ). Research has also found that slow‐paced, traditional and conservative organization cultures (e.g.…”
Section: Motivation and The Place Of Culture In Romancementioning
confidence: 97%
“…Jobs that are characterized by a sexual simmer (Giuffre and Williams ) or a high level of sexual innuendo and flirtation offer a more hospitable climate for romance: for example, restaurants (Salvaggio et al . ). The psychological and structural context of work, for example the norms for sexual behaviour, are important to understanding the antecedents of workplace romance.…”
Section: Motivation and The Place Of Culture In Romancementioning
confidence: 97%
See 2 more Smart Citations